The role of task meaning on output in groups: Experimental evidence - Agnes Bäker; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
This paper analyzes experimentally how the interaction of task meaning and peer presence affects work effort. We build on the experimental designs of Falk and Ichino (2006) and Ariely et al. (2008). Confirming previous results from the literature, we find positive peer effects and negative effects of low task meaning. In addition, we find that peer effects are even stronger if task meaning is low. We conclude that a peer setting is able to overcome the negative effort effect of low task meaning.
Keywords: J20; J30; M50; 330; task meaning; peer effects; experimental economics